Simulación de la concentración de contaminantes atmosféricos provenientes de fuentes continuas para realizar evaluaciones de impacto ambiental. - León Arroyo, José Ricardo (2013)
This paper explores the application of computer tools air dispersion modeling in developing of Environmental Impact Studies and implementing emergency response plans. The most recent legislation at the international level to control technological risks have incorporated the dose criterion in the definition of areas of vulnerability. This involves knowing the concentration and the time at which a person is exposed during the emergency. In this context, this paper develops an implementation of dose calculation in the Gaussian model for the dispersion of pollutants. It also proposes an algorithm that assesses the exposure dose for instantaneous sources for which also produces a computer program in Matlab environment. Finally, we present two examples where these strategies are applied to the determination of exposure doses for both types of sources. From the results obtained and comparing them with literature information it was concluded that the two proposed models are a useful tool if you do not have more sophisticated models.